Pelestarian Bahasa-Sastra Sunda oleh Paguyuban Sastrawati Sunda Patrem (1982-2018) - Ika Ristiana; Amung Ahmad Syahir Muharam (Historia Madania: Jurnal Ilmu Sejarah, 2019)
Paguyuban Sastrawati The Sunda Patrem Sastrawati is the organization of  Sundanese female authors in West Java that was founded on November 4, 1982. Patrem is a Sundanese woman's hairpin used in ancient times. Patrem was then chosen as the name and symbol for the Sundanese literary organization, as well as linking it to the Patrem used by Princess Dyah Pitaloka in the Bubat War which became a symbol of the beauty and strength of Sundanese women. The special characteristic of the Sunda Patrem Sastrawati Circle of Friends is to use Sundanese as the identity of the organization, and to maintain the customs and beliefs of the Sundanese people as Sundanese identity, so the writer is interested in studying the role played by the Sunda Patrem Circle. The purpose of this study is to reveal the role of Sundanese women as writers who contribute in realizing the development of the Indonesian Nation. This research was conducted using the Historical Research Methods (Heuristics, Criticism, Interpretation, and Historiography) with a social and cultural science approach. The Sastrawati Sunda Patrem Circle through its work program has helped the success of the Indonesian government and community program in National Development in the Regional Culture, especially the Sunda Region.